DIMENSI FRAUD DIAMOND TERHADAP KECURANGAN AKADEMIK MAHASISWA - Bahri, Syamsul; Novita, Novita (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2024)
This study aims to prove the effect of fraud diamond dimensions on academic cheating in a hybrid learning system. The method in this study uses Partial Least Square. The object of the study is Trilogi University. Respondents are all active undergraduate students from 2019 to 2022. The population is 1247 from 12 study programs. The research sample consists of 115 undergraduate students who already have a GPA. This study found that pressure and ability have a positive effect on student academic cheating. Opportunity and rationalization have no effect on student academic cheating.